Identity and public realm - Cheshmehzangi, Ali (Elsevier, 2012)
In a very general sense, Identities materialise space to create significance, meaning and spatial relations. In urban design terms, identity is considered to be a fixed point of thought and being or ground of actions. However, as Hall (1989) describes, identity is, in fact, a development or a progression towards creation of inter-relationships between oneself and other and vice versa. Consequently, this paper explores the term ‘identity’ and its implication in an urban context, and also focuses upon the meaning of identity in a public realm to identify how it influences the meaning that people attach to their environments.